The effect of mineral nutrition on yield, nutritional value and consumer safety of radish microgreens under different photoperiods - Shibaeva Tatjana; Rubaeva Alexandra; Sherudilo Elena; Titov Alexander (BIO Web of Conferences, 2023)
The work was aimed to examine the effect of mineral nutrition on yield and content of phytochemicals with antioxidative properties in radish (Raphanus sativus var. radicula) microgreens grown under different photoperiods (16 h and 24 h). Microgreens were supplied with mineralized water or 50% Hoagland nutrient solution. The study has revealed that robust index (RI, dry mass per unit of stem volume) was increased by the presence of mineral nutrition as expected. However, the relationship between the content of phytochemicals that determine nutritional value of radish microgreens and amount of nutrients in the growing media depended on what phytochemical was under consideration. Thus, plants supplied with Hoagland solution had higher chlorophyll and carotenoid content, while plants supplied with water had higher concentration of such antioxidants as anthocyanins and proline and lower nitrate content. Continuous lighting synergistically increased plant response to nutrient deficiency in terms of elevated anthocyanin and proline content and decreased nitrate content, while enhanced RI, chlorophyll and anthocyanin content in plants supplied with nutrient solution. Thus, microgreen productivity and nitrate content as well as some phytochemicals adding nutritional value to radish have opposite dependence on the level of plant nutrient supply, which suggests growers to make a choice between higher yield or higher health benefits to human health and consumer safety of radish microgreens.